Peran Kepuasan Kerja dalam Memediasi Pengaruh Job Enrichment, terhadap Komitmen Organisasional - Suwitra, I Wayan; Premayani, Ni Wayan Wina; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Organizational commitment is the employee engagement that creates a sense of belonging to the workplace. In order for employees to have high organizational commitment to the company, the company needs to pay attention to the factors that influence organizational commitment. The purpose of this study was to determine the effect of job enrichment on organizational commitment, to determine the effect of job satisfaction on organizational commitment, to determine the effect of job enrichment on job satisfaction, and to determine the role of job satisfaction in mediating the effect of job enrichment on organizational commitment.This research was conducted at the Harper Kuta Hotel. The number of samples taken was 57 employees, with a saturated sampling method. Data collection was carried out through interviews and questionnaires. The analysis technique used is path analysis technique (Path Analysis).The results of this study indicate that job enrichment has a positive and significant effect on organizational commitment. Job satisfaction has a positive and significant effect on organizational commitment. Job enrichment has a positive and significant effect on job satisfaction. Job satisfaction mediates the effect of job enrichment on organizational commitment. The theoretical implications of the results of this study provide an understanding that when employees have good job enrichment and job satisfaction, these employees will automatically be committed to their organization.